The balance of intergenerational exchange: correlates of net transfers in Germany and Israel - Litwin, Howard (Springer-Verlag, 2008)
The aim of this study was to examine the net balance of transfers between persons aged 50 and older and their family, taking into account both the exchange of money and the exchange of practical assistance (time). Toward this end, a unique net balance outcome measure was computed by costing the value of time transfers into wage equivalents. The study made use of data from the first wave of the Survey of Health, Ageing and Retirement in Europe (SHARE), and focused upon intergenerational exchange in two specific countries: Germany and Israel. The descriptive findings show that—up to an age of about 80 years—the elderly are net providers of help. The outcome variable was next regressed on a set of relevant predictors identified in the literature on intergenerational transfers and support—among them, sociodemographic background, health, social policy, social network and motivation variables. Holding these variables constant, the balance pattern by age remains valid: respondents aged 50–79 in both settings contributed to their family more than they received. These trends in net transfer exchanges were largely similar across both countries and across regions or population groups within both countries. Women were more likely to have a positive net exchange balance and poorer health was associated with net receiving. However, differences also emerged: social capital was more clearly associated with a positive exchange balance in Israel, transfer motivations shaped transfer behaviors in Germany but not in Israel, and socioeconomic variables seemed to work in opposite directions in the two countries. In sum, the results underscore the generally positive contribution of older people to intergenerational exchange in the family. This outcome holds for both Germany and Israel despite their very different conditions of context.